STUDI PEMANFAATAN AGREGAT SUNGAI DAN DEBU BATU SEBAGAI AGREGAT HALUS PADA CAMPURAN HRS-WC - Alfian, Ifan; Sulandari, Eti; Mayuni, Siti (Jurnal Mahasiswa Teknik Sipil Universitas Tanjungpura, 2016)
The purpose of this study is to find the effect of characteristics Marshall test that use of two different aggregate in asphalt mixture HRS-WC and comparing both types of smooth aggregate on the strength of asphalt mixture. For the composition of the mixture of four types of smooth aggregate used to use the same proportions that uses as much as 55% coarse aggregate, fine aggregate by 40% and the use of filler as much as 5%.It can be seen from the results of the testing we did for smooth aggregate stone dust has the highest stability values of all types of smooth aggregate used is equal to 1440 Kg. In the asphalt content of 6%, but with consideration of the overall results of the test obtained Marshall KAO value of 7.71% with the value of 1340.10 Kg stability, flow value of 4.96 mm, MQ value of 271.10 Kg / mm, VFB the value amounted to 94.30%, the value of VIM 4.85% and for the VMA value amounted to 18.10%.For the use of smooth aggregate that comes from sand, just being grained sand that meets the general specifications of public works by KAO obtained amounted to 7.43% with a value of 1220.00 Kg stability, flow value of 4.10 mm, a value of 297 MQ , 50 Kg / mm, VFB value of 73.60%, VIM value of 5.58%, and the VMA value of21.28%. Keywords: Smooth Aggregate, Mixture composition, Marshall Test